Oil price exposure to asset returns: a disaggregate analysis - Abdul Jalil, Norasibah; Duasa, Jarita; Mat Ghani, Gairuzazmi; Ibrahim, Mansor; yusof, Hamidah (2011)
The paper analyzed oil price exposure on asset returns of eight economic sectors namely- Construction (CON), Consumer (CSU), Finance (FIN), Industrial (IND), Plantation (PLN), Property (PRP), Services (SER), and Mining (TIN). of economy. Two tests, identified as Model 1 and Model 2, were conducted via the Augmented-CAPM (A-CAPM) approach. The first was a symmetric analysis while the second was an asymmetric typed of analysis. The estimated results from Model 1 documented insignificant results in all sector analyses. These findings signified that the stock returns were not exposed to oil price shocks. The estimated results of Model 2 indicated the presence of significant finding in industrial (IND) sector, of the PW analysis. The returns of the IND sector were negatively exposed to change in PW oil price, and it was more significant during periods of oil price increased. In other word, the event of oil price increased significantly reduced the returns of the IND sector.